A synthesis of abemaciclib utilizing a Leuckart–Wallach reaction. Issue 7 (11th February 2015) - Frederick, Michael O.; Kjell, Douglas P.
Graphical abstract: Abstract: A concise total synthesis of CDK 4/6 inhibitor abemaciclib is described. The synthesis uses a Suzuki coupling, followed by a Hartwig–Buchwald amination to join three of the four subunits. The final step is a reductive amination utilizing Leuckart–Wallach conditions. Key to the Leuckart–Wallach reaction was the addition of trimethyl orthoformate to remove water formed during the reaction, allowing the reaction to go to completion.